Effects of accessibility and adequacy of technical vocational education and training equipment on acquisition of employable skills in Uganda. A case of Uganda Technical College - Elgon. - Wanda, Herbert; Edoru, John Michael (Kabale University, 2024)
The Government of Uganda has continued to establish and equip public Technical Vocational Education and Training (TVET) Institutions in the country. However, despite the initiatives, learners have continued to join the industry and claimed to have inadequate employable skills. This poses the question of whether the equipment utilized is adequate and accessed by learners to acquire employable skills. This paper therefore examined the access and adequacy of TVET equipment in Technical Colleges. A descriptive survey design utilizing quantitative and qualitative approaches of research was conducted, with a sample size of 100 learners and 5 instructors were selected. A simple random sampling technique to choose learners responded to the questionnaires and purposive selection of instructors for focus group discussions. Statistical Package for the Social Sciences was used to run descriptive analyses, ordinal regressions, and frequency distribution. Findings on adequacy show that 77% of the learners are availed of equipment not relevant to their program and spend little time practicing on the equipment. In conclusion, TVET equipment was inadequate with limited time spent on practicum, and recommended that Government institutions should undergo into memorandum of understanding with the industry to enable learners to adequately access practice experience on modern equipment relevant to their training.